Akar Sejarah Pemikiran al-Shāṭibī tentang Rukhsah - Makmun Syar'i (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2011)
Al-Shatibi is known in the history of Islam as a prisoner in the theory of Syariah. He wrote al-Muwāfaqāt, his magnum opus. This paper deals with this historic figure by referring to his theory concerning rukhsah; an exemption given to Muslim in performing the rites for certain and acceptable reason. The paper will look at this concept by considering the background in which it is propounded. We believe that his theory is not conceptualized out of the blue. Two keywords will be used to embark on this task, namely 'adam al-ḥaraj and (taṭbīq). The former is about removing the difficulty from man, and the latter is about the application of the Syariah in the live of individual. By using the first concept, the paper will try to reconstruct the fact that in propounding his theory of rukhsan, al-Syatibi always keeps in mind the fact that Islam is revealed mainly to make life easy, and not vice versa. By using the second concept in the meantime, we try to show that the Syari'ah laws?rukhsah included?are revealed to apply (the application Syariah is not always in political context).